Clinical study of serum interleukin-6 in children with community-acquired pneumonia - Ahmed A. Khattab; Muhammad S. El-Mekkawy; Amira M. Shehata; Nermeen A. Whdan (SpringerOpen, 2018)
Background: Community-acquired pneumonia (CAP) is an important childhood killer. Excessive production of cytokines, including interleukin-6 (IL-6), might be associated with severe disease course but pediatric data is limited. Aim: To assess value of IL-6 in predicting CAP severity in children. Methods: A prospective study conducted on 73 children hospitalized for CAP and 15 healthy controls. Pneumonia severity was evaluated according to World Health Organization (WHO) classification, Respiratory Index of Severity Score (RISC), Predisposition, Insult, Response, Organ dysfunction modified (PIROm score), and Pediatric Respiratory Severity Score (PRESS). Serum IL-6 was measured within 24 h of admission. The primary outcome was occurrence of any pneumonia complications or death within 30 days. Results: IL-6 was significantly higher among patients compared with controls. Unlike CRP, IL-6 was significantly higher among children with severe pneumonia as determined by WHO, PRESS, and RISC (p = 0.001 for all). IL-6 was significantly higher among children with PICU admission, mechanical ventilation, shock (p = 0.001 for all), hypoxia (p < 0.001), and lobar consolidation (p = 0.042). IL-6 had positive correlations with PRESS (rs=0.8, P < 0.001), RISC (rs=0.6, p < 0.001), and PIROm (rs=0.59, p < 0.001) while a negative correlation was found with Oxygen saturation [r = −0.61, p = 0.001]. IL-6 was not significantly correlated with CRP. Receiver Operating Characteristic curve (ROC) analysis revealed large area under the curve (AUC) of IL-6 for prediction of severe pneumonia as classified by WHO, PRESS, and RISC (AUC = 0.95, 0.94, and 0.89 respectively). Conclusion: IL-6 appears to be valuable for assessment of CAP severity in children compared with conventional biomarkers. Keywords: Interleukin-6, Community acquired pneumonia, C-reactive protein, Prognosis, Pediatric